Adaptation to chronic hypoxia in triple-negative breast cancer - Hartley, F (2023)
Low levels of oxygen (i.e. hypoxia) are often observed in solid tumours. Hypoxia is able to drive several of the cancer hallmarks and promotes resistance to both radio and chemotherapy, resulting in its association with poor prognosis. Triple-negative breast cancer has the worst prognosis of all breast cancer subtypes with a 5 year survival rate of only 76.7%, and only 10.8% if the cancer has already metastasised. In line with this, triple-negative tumours often have higher levels of hypoxia than their hormone receptor expressing counterparts.